KADAR DAN EKSPRESI TNF YANG TINGGI SEBAGAI FAKTOR RISIKO NYERI NEUROPATI DIABETIK - Thomas Eko P* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION PATHOGENESIS OF PAINFUL DIABETIC NEUROPATHY PDN IS COMPLEX AND STILL POORLY UNDERSTOOD RECENTLY IT HAS BECOME CLEAR THAT PROINFLAMMATORY CYTOKINES PLAY AN IMPORTANT ROLE IN THE PATHOGENESIS AND MAINTENANCE OF PAIN IN PDN